PERAN ADVOKAT SEBAGAI PENEGAK HUKUM DI INDONESIA - Andika Rahmad Siregar; Boy Keke Syahriadi; Tagor Indra Mulia Lubis; Zaidan Azmi; Idham Kholiq Hasibuan (JURNAL ILMIAH NUSANTARA, 2025)
The aim of this study is to provide recommendations and insights related to the integrity of the legal profession, which must be carried out independently, freely, and responsibly in accordance with professional ethical guidelines. The enforcement of law in Indonesia remains a topic of significant interest for discussion. The law enforcement process, which has yet to achieve optimal results, continues to be a subject of debate in both formal and informal forums. The disparity between expectations and reality in the implementation of law in Indonesia raises doubts about the effectiveness of law enforcement, as the law has not yet achieved its intended goals. One of the suspected causes of this issue is the presence of non-legal factors contributing to discrimination, inconsistency, and uncertainty in law enforcement. This situation has the potential to damage the harmonious relationship between society and the law, especially with law enforcement authorities. The approach used in this research is both a legal positivist and conceptual approach. The conclusion of this study suggests that an advocate must maintain their integrity as part of the legal profession and always act in accordance with the professional code of ethics. However, the full implementation of the advocate’s code of ethics still faces challenges, due to the lack of a clear and comprehensive legal framework governing advocacy organizations under the law.